Evaluasi Kinerja Di Badan Perpustakaan, Arsip Dan Dokumentasi Provinsi Sulawesi Utara - Thaib, Sri Maryati; Rumapea, Patar; Tulusan, Femmy (JURNAL ILMIAH SOCIETY, 2016)
The aim of this research are to find and analyze the working performance in Library Office Archives and Documentation at North Sulawesi Province. This research used qualitative method, data were collected by interview and library study. There were ten informants. The data collected were about librarian working performance evaluation then they were analyzed through data triangulation and data reduction. The result showed that the working performance evaluation in Library Office Archives and Documentation at North Sulawesi Province did not run maximal. There are rare of the librarians who graduated from librarian institute and information technology. Irrelevant library collection condition to present day, manual circulation and information tracking tool, and librarian less professionalism were the barriers. Keywords: Performance, library books and professionalism